Anomalous spin relaxation in graphene nanostructures on the high temperature annealed surface of hydrogenated diamond nanoparticles. Issue 35 (25th August 2021) - Joly, V. L. Joseph; Takai, Kazuyuki; Kiguchi, Manabu; Komatsu, Naoki; Enoki, Toshiaki
Abstract : The magnetization relaxation rate of graphene nanostructures created on the surface of hydrogenated nanodiamond by high temperature annealing is explained in terms of a combination of the non-Arrhenius thermal process and the tunneling process. Abstract : The electronic and magnetic structures of diamond nanoparticles with a hydrogenated surface are investigated as a function of annealing temperature under vacuum annealing up to 800–1000 °C. Near edge X-ray absorption fine structure (NEXAFS) spectra together with elemental analysis show successive creation of defect-induced nonbonding surface states at the expense of surface-hydrogen atoms as the annealing temperature is increased above 800 °C. Magnetization and ESR spectra confirm the increase in the concentration of localized spins assigned to the nonbonding surface states upon the increase of the annealing temperature. Around 800 °C, surface defects collectively created upon the annealing result in the formation of graphene nano-islands which possess magnetic nonbonding edge states of π-electron origin. Interestingly, extremely slow spin relaxation is observed in the magnetization of the edge state spins at low temperatures. The relaxation time is well explained in terms of a lognormal distribution of magnetic anisotropy energies instead of the classical Néel relaxation mechanism with a unique magnetic anisotropy energy, in addition to the contribution of the quantum mechanical tunnelling mechanism. The spin–orbit interaction enhanced by the electrostatic potential gradient created at the interface between the core diamond particle and surface graphene nano-islands is responsible for the slow spin relaxation.